Effects of Azadirachta indica on neuropathic pain induced by chronic constriction injury to sciatic nerve of Wistar rat - Biswas, Parijat; Shahnaz, Monira; Akhter, Masuma; Ripa, Arifa Parvin; Ali, Taskina; Rafiq, Kazi (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The research was designed to assess the consequences of Azadirachta indica aqueous leaf extract (AILE) on neuropathic pain in Wister rats and the role of the ATP-dependent potassium channel (KATP) as an underlying mechanism. Materials and Methods: This experimental layout was conducted on Wistar rats (n = 120) having 150 to 200 gm of body weight. On the foundation of the experimental design, rats were divided into group I (normal saline, 5 ml/kg/body weight) and group II (sham surgery and treatment with NS), group III [chronic constriction injury (CCI) in the sciatic nerve; and treated with NS], group IV (CCI and treated with AILE 400 mg/kg body weight), Group V (CCI, pretreated with Glibenclamide 15 mg/kg followed by treated with AILE 400 mg/kg). All the treatments were given once daily for a consecutive 21 days via the oral route, except Glibenclamide. Glibenclamide was given once through the intraperitoneal route on the day of the experiment. Results: Based on the neuropathic pain evaluation test, all groups were again sub-divided into subgroup “a” (walking tract analysis), “b” (cold tail immersion test), “c” (Von Frey test), and “d” (hot plate test). AILE showed a significantly higher sciatic functional index (p < 0.05) in walking track analysis, tail flick latency (p ≤ 0.05) in the cold tail immersion test, and paw withdrawal threshold (p ≤ 0.05) in the Von Frey test compared to CCI control. In addition, a nonsignificant difference in all these above-mentioned variables between the rats with CCI plus AILE and the CCI plus AILE plus glibenclamide group indicated that the KATP channel was not involved in the beneficial analgesic effects of AILE. Conclusions: The outcome of the present study indicates that AILE prevented worsening of neuropathic pain after chronic constriction injury in the sciatic nerve of Wistar rats in which the KATP channel was not involved. J Adv Vet Anim Res 2022; 9(3):359–368 http://doi.org/10.5455/javar.2022.i603